Fabrication of Etoposide-loaded superparamagnetic iron oxide nanoparticles (SPIONs) induced apoptosis in glioma cancer cells. (May 2023) - Wang, Zhihua; Wang, Ye; Li, Hailiang; Lan, Yuanxiang; Zeng, Zhong; Yao, Jian; Li, Mei; Xia, Hechun
Abstract: Recent research has shown that etoposide (ETP), an immunomodulatory medication, can have cytotoxic effects. When accompanied by nano-drug delivery, this possibility can lead to a more effective treatment for cancer. This study involved the delivery of ETP via PDA@SPIONs (termed as ETP-PDA@SPIONs), which are superparamagnetic iron oxide nanoparticles (SPIONs) that have been coated with polydopamine (PDA) and utilized to treat C6 and U87 glioma cancer cell lines. The particle diameter, polydispersive index (PDI), zeta potential, and shape of nanoparticles were determined. The fabricated nanoparticles had a mean particle size of 164 ± 7 nm and a − 37 ± 3 mv zeta potential. Cell lines were tested for sensitivity to PDA@SPIONs, free-ETP, and ETP-PDA@SPIONs. On the cell lines, we tested the proliferation of PDA@SPIONs, free-ETP, and PDA@SPIONs loaded with ETP. The cytotoxicity of ETP-PDA@SPIONs was substantially higher than that of free-ETP-treated cells. The cells' morphological changes were examined by dual staining (acridine orange/ethidium bromide, AO/EB) and nuclear staining methods. Interestingly, this inhibitory impact was not ascribed to the known cellular membrane destruction, cell membrane damage, and reactive oxygen species (ROS). Further tests demonstrated that the nanoparticles substantially impacted mitochondrial functioning, resulting in an aberrant mitochondrial shape, and reduced mitochondrial membrane potential (MMP). Future studies into glioma cancer therapy may want to investigate using the proposed ETP-loaded nanoparticles. Graphical Abstract: ga1 Highlights: We establish that Etoposide with polydopamine coated superparamagnetic iron oxide nanoparticles. The particle diameter, polydispersive index, zeta potential, and shape of nanoparticles were determined. C6 and U87 glioma cells were tested cytotoxicity by MTT assay. The cells' morphological changes were examined by acridine orange/ethidium bromide and nuclear staining. Nanoparticles were induced apoptosis in mitocandrial membrane potential and reactive oxygen species pathway.